Metastability in the Potts model: exact results in the large q limit. (30th June 2020) - Mazzarisi, Onofrio; Corberi, Federico; Cugliandolo, Leticia F; Picco, Marco
Abstract: We study the metastable equilibrium properties of the two-dimensional Potts model with heat-bath transition rates using a novel expansion. The method is especially powerful for large number of state spin variables and it is notably accurate in a rather wide range of temperatures around the phase transition.